IMPACT OF COMMERCIAL BANKS PROFITABILITY ON THE ECONOMIC GROWTH IN NIGERIA (1990-2023) (AUN INTERNATIONAL CONFERENCE, 2025)
The study investigated the impact of commercial banks’ profitability on Nigeria’s economic growth from 1990 to 2023. Gross Domestic Product Growth Rate (GDPGR) was used as the dependent variable, while independent variables included return on assets (ROA), credit to small commercial bank equity (CBE), and prime interest rate (PIR). The study employed secondary data from Central Bank of Nigeria statistical Bulletin (CBN), and Nigerian Deposit and Insurance Corporation (NDIC). The Augmented Dickey-Fuller test confirmed the stationarity of these variables. Using the ordinary least square (OLS) method, the study found that ROA had a negative and insignificant impact on economic growth while PIR had a positive relationship but insignificant effect, while CBE had a negative but significant impact on economic growth. The ANOVA/F-test showed that independent variables collectively influenced GDPGR significantly. The study, therefore, recommended that government and stakeholders should sustain the positive impacts of PIR on economic growth through appropriate fiscal policies, enhancing revenue generation for both the government and commercial banks.